Critical Analysis of the Austin’s Theory in Communication - Afriyanti Simamora; Rizka Aprilya; Vira Budiarti; Yona Syafitri (JELITA, 2020)
A tool of social interaction or a tool of human communication is nothing but language. What is agreed with communication is a place where humans can convey information such as thoughts, ideas, intentions, and emotions. This study discusses the meaning of utterances that carry critical speech acts in different situations. This study research in this journal to examine J. Austin's Speech Theory of Action. This study criticism of Austin's Speech Theory of Action. In researching this journal use qualitative research methods to make it easier for this study and make it easier for readers that there are a number of Austin opinions that are lacking explanation, speech acts are the basic unit of meaning to express meaning of speech that contains a purpose, this journal is made to help students who are less critical in thinking become more critical.